Literature Review: Integration of Morning Dhikr and Mindfulness Parenting to Enhance Executive Function in Children with ADHD - Hasibuan, Wilda Fasim; Utami, Kharisa Hasna; Santoso, Harri; Saputra, Salim; Rochma, Izura (Universitas Muhammadiyah Surakarta, 2025)
This research study seeks to investigate the impact of morning dhikr recitation on executive function, specifically regarding sustained attention and inhibitory control, as well as the influence of mindful parenting on children diagnosed with attention deficit hyperactivity disorder (ADHD). Parenting children with ADHD can provide significant emotional and behavioral challenges, often leading to increased stress, frustration, and fatigue. This research investigates sustained attention and inhibitory control during morning dhikr recitation and its impact on executive function. This study utilizes thematic analysis to identify relevant themes and discourse analysis to assess the importance of morning dhikr. The research synthesizes interdisciplinary insights from psychology, religious studies, and cultural wisdom traditions to clarify how spiritual foundations and indigenous contemplative practices may improve attentive, compassionate, and resilient parenting. The aim is for this literature evaluation to be employed consistently and thoroughly in both governmental and non-governmental ADHD treatment programs